Comportamentos de cidadania organizacional: os efeitos da inteligência emocional e da satisfação no trabalho em organizações públicas - Parcianello, José Adroaldo (2022)
The actions and discretionary gestures practiced by employees in organizations, which go beyond the tasks or attributions formally determined by the position and function of the organization, are considered Organizational Citizenship Behavior (OCB). Several national and international studies consider the OCB as a tool of competitive advantage for organizations, because, from it, it is possible to carry out a strategic management of people. The aim was to investigate the effects of Emotional Intelligence and Work Satisfaction antecedents in relation to Organizational Citizenship Behaviors (OCB), from the perspective of Technical-Administrative Public Servants in Education (TAS) active in federal institutions of higher education (FIHE) . Regarding the method, it was a quantitative, descriptive and exploratory research to be conducted through a survey. The Organizational Citizenship Behavior Scale for Knowledge Workers (OCBS-KW), the Wong and Law Emotional Intelligence Scale (WLEIS-P) and the Job Satisfaction Scale (JSS) were used. The main results found expose the relationship of influence of the antecedents Emotional Intelligence and Satisfaction at Work on the Organizational Citizenship Behaviors for the Technical-Administrative Servers in Education, and the constructs exerted a positive and significant influence on the OCB. Among the antecedents, the one that had the most impact on the OCB was Emotional Intelligence. Of the six hypotheses defined from the theoretical arguments presented, three were confirmed and another three partially confirmed. Thus, by proving the influence of antecedents on Organizational Citizenship Behavior, this study allowed a new look at the OCB, considered an emerging theme in studies on Organizational Behavior. The results, analyzed from the structural equation modeling, demonstrated the interactions between the antecedent constructs and the OCBs in the public sector and that can contribute to the area of people management and to future studies on the subject.